Fecal microbiota transplantation in severe pneumonia: a case report on overcoming pan-drug resistant Klebsiella pneumoniae infection - Zhuang, Liying; You, Yanjing; Zeng, Shenyuan; Yu, Zongyang; Wang, Huijuan; Chen, Meiyan; Wen, Wen (Frontiers in Medicine, 2024)
ObjectiveTo evaluate the therapeutic potential of fecal microbiota transplantation (FMT) in treating severe pneumonia patients with concurrent pan-drug resistant Klebsiella pneumoniae infection.MethodsA case report of a 95-year-old female patient with severe pneumonia, complicated by pan-resistant bacterial infections, is presented. The patient was diagnosed with severe pneumonia caused by COVID-19, along with co-infections of Staphylococcus hominis, Enterococcus faecalis, Candida tropicalis, Pseudomonas aeruginosa, ESBL-producing pan-drug resistant Klebsiella pneumoniae and pan-resistant Acinetobacter baumannii. During hospitalization, the patient underwent comprehensive treatments, including antimicrobials, mechanical ventilation, and fiberoptic bronchoscopic alveolar lavage. FMT was administered following the failure of conventional treatments to resolve recurrent diarrhea, increased sputum production, and persistent pan-drug resistant Klebsiella pneumoniae infection.ResultsPost-FMT, the patient exhibited significant clinical improvement, including reduced sputum production, cessation of diarrhea, and the normalization of respiratory symptoms. Gut microbiota analysis revealed that FMT enhanced the abundance of beneficial microbiota and suppressed Klebsiella pneumoniae, and the patient was successfully discharged after 133 days of hospitalization.ConclusionFMT emerged as a pivotal intervention in the management of this severe pneumonia case, suggesting its efficacy in restoring gut microbiota balance and aiding recovery from multi-drug-resistant infections. This case underscores the potential of FMT as a therapeutic option in severe pulmonary infections, especially in the context of antibiotic resistance in severe pneumonia patients.